DETERMINAN KEPATUHAN ODHA DALAM MENJALANI TERAPI ANTIRETROVIRAL (ARV) - Dian Mahanani; Tonsisius Jehaman; Indrawan Manitu; Rolly Harvie Stevan Rondonuwu (Ensiklopedia Research and Community Service Review, 2026)
Abstract: The Human Immunodeficiency Virus (HIV) remains one of the global public health issues requiring serious attention. HIV remains one of the public health issues requiring serious attention in Indonesia. The purpose of this study was to identify the determinants of adherence to antiretroviral (ARV) therapy among people living with HIV. A cross-sectional study design was used in this research. The study was conducted at Sele Be Solu Regional General Hospital in Sorong City. The study was carried out in September 2025. The sample consisted of 30 participants. Purposive sampling was used. A research questionnaire served as the data collection instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between family support (p-value: 0.000) and self-efficacy (p-value: 0.001) with ARV treatment adherence. It is recommended that patients communicate openly with their caregivers, use simple reminder strategies, and cultivate an awareness that the long-term benefits of ARV therapy far outweigh the perceived barriers.Keywords: Family Support, Self-Efficacy, HIV.